2015
DOI: 10.1111/jora.12206
|View full text |Cite
|
Sign up to set email alerts
|

Configurations of Adolescents' Peer Experiences: Associations With Parent–Child Relationship Quality and Parental Problem Behavior

Abstract: Adolescents' peer experiences embrace behavior, relationship quality, status, and victimization, but studies that account for multiple dimensions are rare. Using latent profile modeling and measures of peer behavior, relationship quality, peer status, and victimization assessed from 1,677 adolescents, four profiles were identified: High Quality, Low Quality, Low Quality Victimized, and Deviant Peers. Multinomial logistic regressions showed that negative parent-child relationships in preadolescence reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Our findings suggest that adolescents who are in families where fathers are more hostile, rejecting, and less warm and supportive might feel that they cannot count on their father to respond if they need help. Therefore, they come to lack trust in interpersonal relationships generally, struggle with emotion regulation skills, and lack confidence in navigating the peer context successfully (Kretschmer et al, 2016; Lieberman, Doyle, & Markiewicz, 1999). Our finding that this association was unique to fathers’ parenting after accounting for mothers’ parenting is consistent with prior research (Bögels et al, 2011) and might be due to more generalized differences in parenting that have been observed in families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that adolescents who are in families where fathers are more hostile, rejecting, and less warm and supportive might feel that they cannot count on their father to respond if they need help. Therefore, they come to lack trust in interpersonal relationships generally, struggle with emotion regulation skills, and lack confidence in navigating the peer context successfully (Kretschmer et al, 2016; Lieberman, Doyle, & Markiewicz, 1999). Our finding that this association was unique to fathers’ parenting after accounting for mothers’ parenting is consistent with prior research (Bögels et al, 2011) and might be due to more generalized differences in parenting that have been observed in families.…”
Section: Discussionmentioning
confidence: 99%
“…Cold, rejecting parenting undermines adolescents’ trust that their parents will be consistent and will intervene when they need help. In the context of these rejecting relationships, children develop internal working models of interpersonal relationships that are characterized by more emotional and behavioral dysregulation, particularly during social interactions (Brody & Ge, 2001; Kretschmer et al, 2016). Previous research indicates that socially anxious youth experience greater parental rejection, greater parental control, and lower parental warmth than nonanxious youth (Bögels, van Oosten, Muris, & Smulders, 2001; Bruch, Rivet, Heimberg, & Levin, 1997; Festa & Ginsburg, 2011).…”
Section: Expanding Our Concept Of Risk: a Social Anxiety Pathway To Amentioning
confidence: 99%
“…Features of problematic parent–child relationship quality often do not operate in isolation. For example, parent–child relationship problems and punitive discipline have been linked to a greater degree of antisocial peer affiliation (Kretschmer et al, 2015; Pike & Eley, 2009). Greater affiliation to antisocial peers may result in greater parent–child problems or vice versa.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…On the other hand, other studies have found that high responsiveness and affection protect adolescents from peer victimization [16,18] because parental affection and warmth encourages a positive parent-child communication and disclosure [32,39]. Furthermore, positive family relationships, characterized by high parental involvement, family support, positive communication, and cohesion, are related to a reduced risk for engaging in peer aggression [11,15,40] and victimization [31], while bully-victims reported lower levels of parental support compared to aggressors and victims [41].…”
Section: Parenting Dimensions and Peer Aggressionmentioning
confidence: 98%